Mechanical properties of compressed earth blocks reinforced with glass fibers and palm fibers: Experiments and simulation - Fidjah Abdelkader; Rabehi Mohamed; Kezrane Cheikh; Rachid Rabehi (The Journal of Engineering and Exact Sciences)
The civil and mechanical engineers are interested in studying how much load structures can support. Recently, the use of environmentally friendly materials has become widely spread in the field of construction because they do not contribute to the propagation of greenhouse gases, unlike cement construction. In this research, we try to address the problem of the fragility of clay bricks. We use the compressed earth technique and add palm fibers and glass fibers. We want to know the effect of adding these fibers on density, speed of sound transmission rate, and stresses. Preliminary results show the addition of 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% of palm fibers and glass fibers, respectively. The density value increases between 1.1% and 11%. The speed of sound increases between 2.1% and 13.7%, and the stress value increases between 8.6% and 41%. These results enable us to set limits for the loads supported and borne by the walls built with these bricks.